(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2024)
Purpose: This paper analyses economic and social impact of fiscal austerity policies on economic growth and income distribution. In response to the European public debt crisis, austerity measures were implemented in 2010 to decrease the budget deficit and avoid the default of the government debt, but have also caused negative effects on the whole economy. Methodology: In order to evaluate the effectiveness of fiscal austerity, the synthetic control method (SCM) is applied by creating a synthetic counterfactual from European countries. Greece is used as an example to assess the impact of the aforementioned policy due to having experienced fiscal consolidation to a much larger extent than other crisis-affected countries. Results: Fiscal austerity causes a decline in real GDP per capita compared to its pre-austerity level. Additionally, it results in higher unemployment and a more unequal distribution of income in the initial years following the treatment. Conclusion: The objective of fiscal austerity, i.e. the reduction of the debt-to-GDP ratio, is frequently not achieved due to negative effects of these measures on GDP. Fiscal austerity may occasionally be unavoidable, but even in these cases, deliberate measure-taking is required to prevent the increase in unemployment and income inequality, as witnessed after the global financial crisis.